Metal to insulator transition in Ba2Ge2Te5: Synthesis, crystal structure, resistivity, thermal conductivity, and electronic structure. (March 2022) - Jana, Subhendu; Ishtiyak, Mohd; Govindaraj, Lingannan; Arumugam, Sonachalam; Tripathy, Bikash; Malladi, Sairam K.; Niranjan, Manish K.; Prakash, Jai
Highlights: Single-phase polycrystalline Ba2Ge2Te5 was synthesized for the first time. The crystal structure was confirmed by Rietveld refinement and SCXRD studies. The resistivity measurements show metal to insulator transition below 18 K. The thermal conductivity study of Ba2 Ge2 Te5 shows a low value of 0.41 Wm–1K–1 at 773 K. Electronic structure calculations suggest a narrow bandgap for Ba2 Ge2 Te5 . Abstract: A monophasic polycrystalline sample of Ba2 Ge2 Te5 has been synthesized for the first time using the sealed tube solid-state method. The Rietveld refinement of a polycrystalline Ba2 Ge2 Te5 and a single crystal X-ray diffraction study confirm that Ba2 Ge2 Te5 crystallizes in the orthorhombic polar C 2 v 9 - Pna 21 space group. Each of the Ge atoms in the Ba2 Ge2 Te5 structure is covalently connected to one Ge and three Te atoms making one-dimensional (1D) chains of 1 ∞ [Ge2 Te5 ] 4− that are separated by Ba 2+ cations. The (Ba 2+ )2 (Ge 3+ )2 (Te 2− )5 can be charge-balanced as per the Zintl-Klemm concept. A resistivity study of Ba2 Ge2 Te5 shows a metallic behavior till 18 K below which metal to insulator transition was observed. Thermal conductivity of Ba2 Ge2 Te5 was found to decrease gradually on heating the sample with a minimum of about 0.41 Wm –1 K –1 at 773 K. The DFT studies predict semiconducting nature for Ba2 Ge2 Te5 with a narrow indirect bandgap of about 0.6 eV. Graphical abstract: Image, graphical abstract